Managing Complicated Diverticular Disease in 2014 - Marek Soltes; Dorin Popa; Abe Fingerhut; Chadli Dziri (European Medical Journal Gastroenterology, 2014)
Complicated diverticular disease refers to patients who present with abscess, peritonitis, bleeding, fistula, or bowel obstruction. Management paradigms for these complications have changed enormously in the last 20 years. Surgical options include primary resection with or without anastomosis, exteriorisation of the perforation as the site of diversion, and more and more in recent years, simple lavage and drainage. The different classifications, the indications and techniques of interventional radiology, and endoscopy, as well as other minimally invasive or traditional surgical treatment of these complications are covered in this review.